Use of olokizumab, a direct interleukin 6 inhibitor, in the treatment of rheumatoid arthritis: real-world evidence - P. A. Shesternya; A. I. Zagrebneva; O. V. Antipova; Yu. V. Arbuzova; I. G. Bannikova; L. V. Belozertseva; E. A. Bogdanova; S. A. Bykova; E. A. Vasilenko; I. B. Vinogradova; S. Yu. Davidyan; O. E. Epifanova; et al. (Современная ревматология)
Objective: To study the efficacy and safety of olokizumab (OKZ) in patients with rheumatoid arthritis (RA) in real-life clinical practice.Material and methods. The observational program was conducted in 73 centers across Russia from Dec 1, 2022 to Jan 31, 2025. It was based on a retrospective analysis of real clinical practice data. Information on patients was collected and analyzed at baseline and after 1, 6, and 12 months of treatment.Results and discussion. A total of 1,576 patients (81.7% women) with RA, aged 55.0 [44.0; 63.0] years and with RA duration of 100.0 [50.0; 156.0] months, were included in the program. After 6 and 12 months of OKZ therapy, the treatment target (remission/low activity) was achieved in 63.3% and 79.8% of patients by DAS28-CRP, and in 55.4% and 75.5% by CDAI respectively. Gender, age, seropositivity, and use of biologic disease-modifying antirheumatic drugs did not significantly affect the achievement of the treatment goal. During the observation period, a significant proportion of patients were able to discontinue glucocorticoids (GCs): 51.1% of patients received GCs initially, after 6 months, 27.6% of patients still received GCs, and after 12 months, 17.0%. During the observation, OKZ treatment was discontinued in 148 (9.5%) patients: in 50 (3.2%) patients due to insufficient efficacy, in 63 (4.0%) patients due to adverse events, and in 35 (2.2%) patients due to other reasons. Conclusion. IL-6 inhibition with OKZ is both effective and safe for achieving RA therapy goals in real-world clinical settings.